Kiss-and-Run Is a Significant Contributor to Synaptic Exocytosis and Endocytosis in Photoreceptors - Wen, Xiangyi; Saltzgaber, Grant W.; Thoreson, Wallace B. (Frontiers in Cellular Neuroscience, 2017)
Accompanying sustained release in darkness, rod and cone photoreceptors exhibit rapid endocytosis of synaptic vesicles. Membrane capacitance measurements indicated that rapid endocytosis retrieves at least 70% of the exocytotic membrane increase. One mechanism for rapid endocytosis is kiss-and-run fusion where vesicles briefly contact the plasma membrane through a small fusion pore. Release can also occur by full-collapse in which vesicles merge completely with the plasma membrane. We assessed relative contributions of full-collapse and kiss-and-run in salamander photoreceptors using optical techniques to measure endocytosis and exocytosis of large vs. small dye molecules. Incubation with small dyes (SR101, 1 nm; 3-kDa dextran-conjugated Texas Red, 2.3 nm) loaded rod and cone synaptic terminals much more readily than larger dyes (10-kDa Texas Red, 4.6 nm; 10-kDa pHrodo, 4.6 nm; 70-kDa Texas Red, 12 nm) consistent with significant uptake through 2.3-4.6 nm fusion pores. By using total internal reflection fluorescence microscopy (TIRFM) to image individual vesicles, when rods were incubated simultaneously with Texas Red and AlexaFluor-488 dyes conjugated to either 3-kDa or 10-kDa dextran, more vesicles loaded small molecules than large molecules. Using TIRFM to detect release by the disappearance of dye-loaded vesicles, we found that SR101 and 3-kDa Texas Red were released from individual vesicles more readily than 10-kDa and 70-kDa Texas Red. Although 10-kDa pHrodo was endocytosed poorly like other large dyes, the fraction of release events was similar to SR101 and 3-KDa Texas Red. We hypothesize that while 10-kDa pHrodo may not exit through a fusion pore, release of intravesicular protons can promote detection of fusion events by rapidly quenching fluorescence of this pH-sensitive dye. Assuming that large molecules can only be released by full-collapse whereas small molecules can be released by both modes, our results indicate that 50-70% of release from rods involves kiss-and-run with 2.3-4.6 nm fusion pores. Rapid retrieval of vesicles by kiss-and-run may limit membrane disruption of release site function during ongoing release at photoreceptor ribbon synapses.